Bipolar vessel sealer versus conventional suturing in non-descent vaginal hysterectomy: comparative study - Sahu, Mahija; Goru, Harika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The aim and objective of the study is to compare bipolar vessel sealer method with conventional suturing technique in non-descent vaginal hysterectomy. Methods: A prospective observational study was done in the department of obstetrics and gynaecology, S. C. B. Medical College and Hospital, a tertiary care centre, Cuttack, Odisha, in a period from, April 2019 to October 2020. A total of 100 patients fit under inclusion criteria were posted for non-descent vaginal hysterectomy after taking an informed consent. They were divided into (group A) conventional suturing group and (group B) bipolar vessel sealer group, using a randomised computer method. The statistical analysis of data obtained was done using statistical package for the social sciences (SPSS) version 18 software. Results: In the present study the mean procedure time taken in minutes for NDVH using bipolar vessel sealer (BVS) was significantly shorter than suture group (57.54±12.851 versus 29.26±8.808; p<0.001), the mean intraoperative blood loss in ml was also significantly lesser in BVS group (5.96±1.24 versus 3.50±0.73; p<0.001). The mean post-operative pain scores using visual analogue scale (VAS) (0-10) also showed statistically significant reduction in BVS group when observed on immediate post-operative day (POD) (3.50±0.73 versus 5.96±1.24; p<0.001). There was statistical reduction of pain even on POD1, POD2, and POD3 also. The length of hospital stay in days was also significantly shorter in BVS group when compared to suture group (2.10±0.58 versus 5.00±0.404; p<0.001). Conclusions: The bipolar vessel sealer proved superior to conventional suturing in regards to time taken for operating procedure, intraoperative blood loss, post-operative pain (VAS 0-10) and length of hospital stay. The mean post-operative haemoglobin and packed cell volume (PCV) values both were higher in vessel sealer group compared to suturing group although statistical significance was not attained.